Evaluation of medium access and a positioning system in wireless underground sensor networks - Conceição, Sérgio (2016)
Wireless Underground Networks (WUN) have many applications, such as border surveillance, agriculture monitoring, and infrastructure monitoring. Recent studies have shown that they are feasible and have deployment advantages over wired networks, but only a few WUN evaluations in multiple access scenarios have been done. This paper presents a simulation study on medium access for a WUN with 4 nodes buried, and one node aboveground. The simulations were carried out using the ns-3 simulator and they evaluate both Wi-Fi, and Lr-Wpan networks for dry and wet soils. We verified that for the same number of concurrent nodes, the use of the RTS/CTS mechanism has a much higher influence than the soil water content. Furthermore, a study about the feasibility of using Wi-Fi fingerprinting for positioning above the ground based on the buried infrastructure revealed promising results.